THE RELATIONSHIP BETWEEN INTENSITY IN USING MOBILE LEARNING TOOL IN LEARNING ENGLISH AND THE STUDENTS’ GRADE POINT AVERAGE: A Correlation Research - Nurhidaya; Natsir, Ratu Yulianti (FKIP Unismuh Makassar, 2018)
The objective of the research was to find out the relationship between intensity in using mobile learning tool in learning English and the students’ grade point average at the third, fifth, and seventh semester students of English department in Muhammadiyah University of Makassar. The research design was correlational research. The total number of sample was 60 students. The researcher used questionnaire as instrument. The research findings shown that the classification of students’ intensity in using mobile learning tool at the third, fifth, and seventh semester students of English Department in Muhammadiyah University of Makassar was fair with mean score 63.25, and the classification of the students’ grade point average was Cumlaude with the mean score with mean score 3.54. The researcher conclude that there was no correlation between intensity in using mobile learning tool in learning English and the students’ grade point average at the third, fifth, and seventh semester students of English department in Muhammadiyah University of Makassar. The Pearson correlation values of students Intensity in using mobile learning tool in learning English and the students’ grade point average were 0.097, 0.132, 0.077, and 0.087